Mental imagery-based episodic simulation amplifies motivation and behavioural engagement in planned reward activities. (October 2021) - Ji, Julie L.; Geiles, Dylan; Saulsman, Lisa M.
Abstract: Preliminary evidence suggests mental imagery-based episodic simulation of planned reward activities may amplify motivation and promote greater behavioural engagement, particularly for activities with high motivational barriers (Renner, Murphy, Ji, Manly, & Holmes, 2019). This study conducted a conceptual replication and extension of Renner et al. (2019). N  = 81 first-year university students self-selected and scheduled two reward activities (one hedonic, one mastery) for the following week before being randomly allocated to either an Imagery-Experiential elaboration condition ( n  = 27), a Verbal-Reasoning elaboration condition ( n  = 28), or a Scheduling-only Control condition ( n  = 26). Following the lab session, all participants received standardized daily prompts to complete daily activity diaries online for seven days. The Imagery - Experiential condition reported greater increases in anticipatory pleasure (state mood), anticipated pleasure, and self-reported motivation compared to the Scheduling-only Control condition, and greater increases in anticipatory pleasure (state mood), but not anticipated pleasure or motivation, relative to the Verbal-Reasoning condition. Consistent with Renner et al. (2019), the Imagery-Experiential condition, but not the Verbal-Reasoning condition, reported more frequent engagement in high motivational barrier activities than the Scheduling-only Control condition. Exploratory mediational analyses suggested that mental imagery may exert unique motivational impacts via its impact on anticipatory pleasure (state mood), although indirect effects were only observed for self-reported motivation change in the lab, with real world behavioural effects falling short of statistical significance. Highlights: Imagery-Experiential condition led to higher completion of high-barrier activities. Greater mental imagery use was associated with greater increases in anticipatory pleasure. Mental imagery's impact on anticipatory pleasure may drive motivational effects.